A digitally controlled AGC loop circuitry for GNSS receiver chip with a binary weighted accurate dB-linear PGA. (March 2015) - Jin, Gang; Zhuang, Yiqi; Yin, Yue; Cui, Miao
Abstract A novel digitally controlled automatic gain control (AGC) loop circuitry for the global navigation satellite system (GNSS) receiver chip is presented. The entire AGC loop contains a programmable gain amplifier (PGA), an AGC circuit and an analog-to-digital converter (ADC), which is implemented in a 0.18 μm complementary metal-oxide-semiconductor (CMOS) process and measured. A binary-weighted approach is proposed in the PGA to achieve wide dB-linear gain control with small gain error. With binary-weighted cascaded amplifiers for coarse gain control, and parallel binary-weighted trans-conductance amplifier array for fine gain control, the PGA can provide a 64 dB dynamic range from −4 to 60 dB in 1.14 dB gain steps with a less than 0.15 dB gain error. Based on the Gaussian noise statistic characteristic of the GNSS signal, a digital AGC circuit is also proposed with low area and fast settling. The feed-backward AGC loop occupies an area of 0.27 mm2 and settles within less than 165 μs while consuming an average current of 1.92 mA at 1.8 V.